Biografier på scenen: Etik og subjektivitet i virkelighedsteatret - Byrdal Jørgensen, Tine (Peripeti, 2014)
Through an analysis of the performance Gardenia the article discusses the negotiation between aesthetics and ethics in contemporary documentary theatre. Gardenia is a performance with and about aging transvestites. The author combines Lévinas’ ethics with a poststructural understanding of the subject in order to methodically grasp how the performance is activating an ethical relationship between the Other on stage and the spectator.